Solving an electrically conducting nanofluid over an impermeable stretching cylinder problem with a spectral reproducing kernel method - Foroutan, M. R.; Hashemi, M. S.; Rezapour, Shahram; İnç, Mustafa; Habibi, F. (Springer, 2024)
In this paper, a nonlinear mechanical system of ordinary differential equations (ODEs) with multi-point boundary conditions is considered by a novel type of reproducing kernel Hilbert space method (RKHSM). To begin, we define the unknown variables in terms of the reproducing kernel function. The roots of the Shifted Chebyshev polynomials (SCPs) are then utilized to collocate the resulting system. Finally, Newton's iterative method is employed to find the unknown expansion coefficients. The solutions of this system of equations, which arise from the flow of an electrically conducting nanofluid over an impermeable stretching cylinder, are numerically analyzed, and convergence analysis is discussed to demonstrate the reliability of the presented method (PM). Tables and figures are provided to further discuss the solutions and assess the effectiveness of the method in comparison to other techniques in the literature.
Keywords: RKHSM; Shifted Chebyshev polynomials; Convergence analysis; Electrically conducting nanofluid; Nonlinear system of boundary value problems (BVPs)